Adrenal Ganglioneuroma- A Rare Site Entity - Byna Syam Sundara Rao; Vissa Shanthi; Nandam Mohan Rao; Bhavana Grandhi; R Sujitha (Journal of Clinical and Diagnostic Research, 2019)
Ganglioneuroma is a rare lesion reported in many organs including adrenal gland. Adrenal ganglioneuroma is a rare benign sympathetic tumour which originates from Adrenal medulla. The adrenal gland tends to be unusual site but few cases have been reported in the literature. Here, the present authors report a case of Adrenal ganglioneuroma in 35-year-old male. He presented with complaints of diarrhoea and mild pain in abdomen. After abdominal CT scan, the patient underwent laparoscopic right adrenalectomy. Diagnosis was confirmed by histopathological examination as adrenal ganglioneuroma.